APIP Authority and Public Accountability: Institutional Effectiveness in DKI Jakarta Provincial Government - Ronny Berty Talapessy; Murtir Jeddawi; Hyronimus Rowa; Baharuddin Thahir (Equivalent: Jurnal Ilmiah Sosial Teknik, 2026)
Background: … Objective: This study aims to analyze the effectiveness of the Government Internal Supervisory Apparatus (APIP) authority in enhancing accountability within the Provincial Government of the Special Capital Region of Jakarta. Methods: The research employs a qualitative approach using normative-institutional analysis and public policy review. Data were examined through document analysis, APIP capability reports, SPIP maturity evaluations, and recent academic literature. Results: The findings reveal that the effectiveness of APIP authority is not solely determined by regulatory power, but by institutional capacity, auditor independence, leadership commitment, SPIP maturity, and risk-based supervisory integration. Although APIP authority in Jakarta is normatively adequate, its implementation faces structural challenges, including limited human resources, bureaucratic intervention, and weak follow-up on audit recommendations. Strengthening APIP capability to Level 3 and above, transforming supervisory culture, and implementing digital internal audit systems are key determinants of sustainable public accountability improvement. Conclusion: The study concludes that internal oversight reform must be oriented toward integrity-based governance and risk management frameworks.